The effect and safety of Tai Chi on bone health in postmenopausal women: A meta-analysis and trial sequential analysis - Liu, Xiaobo; Jiang, Chengzhi; Fan, Rong; Liu, Tianyu; Li, Yuxi; Zhong, Dongling; Zhou, Luxiang; Liu, Tao; Li, Juan; Jin, Rongjiang (Frontiers in Aging Neuroscience, 2022)
Background Tai Chi may be a promising exercise to prevent and control bone loss in postmenopausal women. This meta-analysis and trial sequential analysis aimed to evaluate the effect and safety of Tai Chi on bone health in postmenopausal women. Method Seven databases were searched from their inceptions to 11 May 2022 to collect randomized controlled trials (RCTs) investigating the effect and safety of Tai Chi on bone health in postmenopausal women. Two independent reviewers identified the eligible studies, extracted data, and assessed the risk of bias of included studies using the revised Cochrane risk-of-bias tool for randomized trials. The primary outcome was the bone mineral density (BMD), and secondary outcomes included bone turnover markers and calcaneus quantitative ultrasound. Subgroup analyses were conducted based on the duration of Tai Chi. Sensitivity analyses and publication bias assessment were performed. RevMan software (version 5.4.1) and R software (version 3.6.1) were used for data synthesis. The certainty of evidence was rated with the Grading of recommendations assessment, development, and evaluation (GRADE) system. We also performed the trial sequential analysis to evaluate the reliability of the evidence. Results A total of 25 reports involving 24 studies were included. Four studies were considered as high overall risk of bias, and the rest were some concerns. Among included studies, there were three comparisons including Tai Chi vs. non-intervention, Tai Chi vs. other exercises, and Tai Chi plus nutraceutical vs. nutraceutical. Compared with non-intervention, Tai Chi was more effective to improve BMD of lumbar spine (MD = 0.04, 95% CI 0.02 to 0.07, I2 = 0%, low certainty), femoral neck (MD = 0.04, 95% CI 0.02 to 0.06, I2 = 0%, low certainty), and trochanter (MD = 0.02, 95% CI 0.00 to 0.03, I2 = 0%, very low certainty), but there was no significant difference in increasing the BMD of Ward's triangle (MD = 0.02, 95% CI −0.01 to 0.04, I2 = 0%, very low certainty). Trial sequential analysis showed that the effect of Tai Chi vs. non-intervention on the BMD of lumbar spine and femoral neck was reliable, but the effect on the BMD of trochanter and Ward's triangle needed further verification. The subgroup analyses suggested that Tai Chi training for over 6 months had greater improvement in BMD of the lumbar spine, femoral neck, and trochanter than non-intervention. No significant differences were observed in the above outcomes of Tai Chi vs. other exercises, and Tai Chi plus nutraceutical vs. nutraceutical. There was insufficient evidence to support the effect of Tai Chi on bone turnover markers and calcaneus quantitative ultrasound. Few Tai Chi relevant adverse events occurred. Conclusion Tai Chi may be an optional and safe exercise for improving BMD loss in postmenopausal women, and practicing Tai Chi for more than 6 months may yield greater benefits. However, more rigorously designed RCTs are required to verify the benefits and to explore the optimal protocol of Tai Chi exercise for bone health. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=309148, identifier: CRD42022309148.